Housing Ranking: a model of equilibrium between buyers and sellers expectations - Roberto Cervelló Royo; Fernando García García; Francisco Guijarro-Martínez; Ismael Moya-Clemente (European Regional Science Association (ERSA), 2011)
The equilibrium set of housing units (alternatives) can be characterized from the standpoint of both the demander and the supplier. The current work describes an application of the multicriteria single price model to the ranking of alternatives. By a generalization of the single price model and from both viewpoints an efficiency index can be calculated. We demonstrate how, in equilibrium, the two viewpoints result inevitably in inverse orders of ranking. The model is illustrated by a sample of housing units in the city of Valencia, Spain.
Keywords: 330